2013
DOI: 10.1088/0004-637x/769/1/3
|View full text |Cite
|
Sign up to set email alerts
|

FIRST SPECTROSCOPIC EVIDENCE FOR HIGH IONIZATION STATE AND LOW OXYGEN ABUNDANCE IN Lyα EMITTERS,

Abstract: We present results from Keck/NIRSPEC and Magellan/MMIRS follow-up spectroscopy of Lyα emitters (LAEs) at z = 2.2 identified in our Subaru narrowband survey. We successfully detect Hα emission from seven LAEs, and perform a detailed analysis of six LAEs free from AGN activity, two out of which, CDFS-3865 and COSMOS-30679, have [O ii] and [O iii] line detections. They are the first [O ii]-detected LAEs at high-z, and their [O iii]/[O ii] ratios and R23-indices provide the first simultaneous determinations of ion… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
177
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(196 citation statements)
references
References 133 publications
(224 reference statements)
18
177
1
Order By: Relevance
“…Their EW(Hα)/EW(Lyα) ratios (∼14) are instead comparable with some high-excitation LAEs at higher redshift (e.g., z ∼ 2 Finkelstein et al 2011;Nakajima et al 2013). Compared with model predictions (e.g., Schaerer 2003), these EW(Hα)/EW(Lyα) ratios are in good agreement with tracks for instantaneous burst models with young ages (∼10 7 yr) and low metallicities (see Nakajima et al 2013, their Fig. 10), probably superposed with a more constant (e.g., exponentially declining) underlying star formation history (e.g., Amorín et al 2012a).…”
Section: Lyman-alpha Emission In Eelgsmentioning
confidence: 72%
See 2 more Smart Citations
“…Their EW(Hα)/EW(Lyα) ratios (∼14) are instead comparable with some high-excitation LAEs at higher redshift (e.g., z ∼ 2 Finkelstein et al 2011;Nakajima et al 2013). Compared with model predictions (e.g., Schaerer 2003), these EW(Hα)/EW(Lyα) ratios are in good agreement with tracks for instantaneous burst models with young ages (∼10 7 yr) and low metallicities (see Nakajima et al 2013, their Fig. 10), probably superposed with a more constant (e.g., exponentially declining) underlying star formation history (e.g., Amorín et al 2012a).…”
Section: Lyman-alpha Emission In Eelgsmentioning
confidence: 72%
“…Comparing their Lyα and Hα equivalent widths (EW(Hα) = 320−580 Å), these galaxies are among those with larger EW(Hα) low-z LAEs in the catalog of Cowie et al (2010). Their EW(Hα)/EW(Lyα) ratios (∼14) are instead comparable with some high-excitation LAEs at higher redshift (e.g., z ∼ 2 Finkelstein et al 2011;Nakajima et al 2013). Compared with model predictions (e.g., Schaerer 2003), these EW(Hα)/EW(Lyα) ratios are in good agreement with tracks for instantaneous burst models with young ages (∼10 7 yr) and low metallicities (see Nakajima et al 2013, their Fig.…”
Section: Lyman-alpha Emission In Eelgsmentioning
confidence: 93%
See 1 more Smart Citation
“…This makes physical conditions in the star forming regions in Mrk 22 similar to those in the extreme star forming galaxies. Nakajima et al (2013) and Nakajima (2013) indicated that these extreme conditions can be produced in several ways such as density bounded HII regions, very high ionization parameters due to presence of hard ionizing sources, and low metallicity. The presence of WR stars in Mrk 22 and in some GP galaxies indicates high ionization parameter in these galaxies.…”
Section: Comparison With Extreme Star-forming Galaxies At Higher Redhmentioning
confidence: 99%
“…Large enough statistics is needed to confirm this idea. The galaxies with very low metallicity share many properties of Lyα emitting galaxies and Ly-break galaxies (Prochaska et al 2003;Nakajima et al 2013;Shirazi et al 2014;Shapley et al 2015). Thanks to the fact that XMDs can be excellent local proxies for their high-z counterparts.…”
Section: Introductionmentioning
confidence: 99%